NATIVE OR NON NATIVE: STUDENTS’ PREDILECTION OF THEIR ENGLISH TEACHER - Eka Afrida Ermawati; Fitriyah Dewi Wulandari (Magister Scientiae, 2019)
A debate on the effectiveness of Native English Teacher (NEST) and Non Native English Teacher (NNEST) has been an outstanding and continuous issue. The debate becomes more interesting since there are differences in some research findings about which one is more effective in teaching English. Therefore, this present research wants to investigate students’ predilection about the effectiveness of their Native and Non Native English speaking teachers’ in teaching English and its relation towards the students’ achievement in learning and comprehending the materials. A survey was conducted by distributing a questionnaire towards students of MAN 1 Kraksaan- Probolinggo. The result of the survey shows that students believe that having NEST is more preferable if they want to be successful in learning English.